Molecular Genetics of Bartter Syndrome - Fazilaty, Hassan; Behnam, Babak (Journal of Pediatric Nephrology, 2014)
<!--[if gte mso 9]> <![endif]--> Bartter syndrome (BS) is a heterogeneous disorder, caused by mutations in several genes which mostly encode proteins involved in ions transportation across renal cells in the thick ascending limb of the nephron. It is characterized by deficient renal reabsorption of sodium and chloride, which results in a group of certain symptoms. Different types of BS can be distinguished from different clinical manifestations, and most importantly, via analyzing possible affected gene(s) for its confirmation. A close associated syndrome which was primarily considered as a mild variant of BS, Gitelman syndrome (GS), is characterized by hypokalemic metabolic alkalosis with hypocalciuria, and hypomagnesemia. In this review, we discuss different features of BS and also GS, including clinical and genetic alterations which correspond to each type. <span style="font-size: 10.0pt; line-height: 115%; font-family: 'Cambria','serif'; mso-ascii-theme-font: major-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: major-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords:<span style="font-size: 10.0pt; line-height: 115%; font-family: 'Cambria','serif'; mso-ascii-theme-font: major-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: major-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Bartter Syndrome; Molecular Genetics; Child. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->